2006
DOI: 10.4049/jimmunol.177.8.4966
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibition of T Cell Activation by TIM-2

Abstract: T cell Ig and mucin domain protein 2 (TIM-2) has been shown to regulate T cell activation in vitro and T cell-mediated disease in vivo. However, it is still not clear whether TIM-2 acts mainly to augment T cell function or to inhibit it. We have directly examined the function of TIM-2 in murine and human T cell lines. Our results indicate that expression of TIM-2 significantly impairs the induction of NFAT and AP-1 transcriptional reporters by not only TCR ligation but also by the pharmacological stimuli PMA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…Second, the murine TAPR locus contains five genes that are absent from the human locus, including TIM-2 which is very closely homologous to TIM-1 (1). We and others have shown that TIM-2 is a negative regulator of T cell activity (15,16,21) and a recent study has shown that TIM-2 can function by blocking CD3/CD28-mediated costimulation of T cells (21). It is possible that TIM-2 acts to block TIM-1-mediated signaling in mice as well.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the murine TAPR locus contains five genes that are absent from the human locus, including TIM-2 which is very closely homologous to TIM-1 (1). We and others have shown that TIM-2 is a negative regulator of T cell activity (15,16,21) and a recent study has shown that TIM-2 can function by blocking CD3/CD28-mediated costimulation of T cells (21). It is possible that TIM-2 acts to block TIM-1-mediated signaling in mice as well.…”
Section: Discussionmentioning
confidence: 99%
“…Jurkat, D10, and 293T cells were cultured and transiently transfected as previously described (14,19,22). Luciferase assays were conducted as described previously (18,22).…”
Section: Methodsmentioning
confidence: 99%
“…Luciferase reporter constructs have been described previously (14,19). Wild-type murine Tim-3 cDNA was obtained by reverse transcription-PCR (RT-PCR), starting with whole-spleen RNA made from C57BL/6 mice.…”
Section: Methodsmentioning
confidence: 99%
“…The first involves a receptor identical to TIM-2 (member of the T-cell immunoglobulin and mucin-domain gene family) that specifically binds extracellular H-subunit rich ferritins followed by the internalization of H-subunit rich ferritins, and is expressed in B-cells and in non-haematopoietic organs such as the liver and kidney. Internalization of the H-subunit rich ferritins resulted in immunosuppression by inhibiting T-cell activation (Knickelbein et al, 2006). The second receptor that binds H-subunit rich ferritins is transferrin receptor 1.…”
Section: Immune Modulation By Secreted H-subunit Rich Ferritinsmentioning
confidence: 99%